Maintaining the Indigenous Udmurt Language beyond the Community: An Autoethnographic Analysis - Svetlana Edygarova (Languages)
In this article, I emphasize the importance of maintaining and transmitting indigenous languages to the next generations, and I explore the motivations and difficulties of indigenous language speakers to do so when living far away from their native language community. The article is an autoethnographic analysis that amplifies the insider’s perspective and reflects on my own thoughts, perceptions, and emotional reactions regarding my language use practices. Specifically, I analyze the use of the Udmurt language with my children and the process of writing a blog in Udmurt. As a researcher of the Udmurt language, I use my previous sociolinguistic studies in the analysis and place it within the broader context of indigenous peoples from Russia. Indigenous languages often involve the use of multiple languages simultaneously, including language mixing, which is entirely natural. In societies with a monolingual language ideology, such practices are seen as signs of linguistic incompetence, leading to feelings of shame or inferiority among indigenous speakers. This negatively impacts the preservation of indigenous languages. Raising sociolinguistic and emotional awareness about how indigenous languages function and sharing personal experiences, including negative ones, can help overcome these challenges.